physicscatalyst.com logo





Quadratic Formula Worksheet




For the Quadratic equation
$ax^2 +bx +c =0$
Where a, b and c are real numbers and a ≠0
Roots of the quadratic equation is given by Quadratic Formula
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$


Question 1. State which all quadratic equations have real roots, no real roots
a. $x^2 + 8x+7=0$
b. $3x^2 +5x+1=0$
c. $9x^2 +x -3=0$
d. $11x^2 +5x+1=0$
e. $10x^2 +3x+7=0$
f. $2x^2 -6x+3=0$
g. $2x^2 -x-2=0$
Solution
Nature of roots of Quadratic equation
S.no
Condition
Nature of roots
1
$b^2 -4ac > 0$
Two distinct real roots
 
2
$b^2-4ac =0$
One real root
3
$b^2-4ac < 0$
No real roots
 
Real roots: :(a), (b), (c),(d) ,(e),(f),(g)
No real roots : (d) ,(e)

Question 2. Find the roots of the quadratic equation using Quadratic Formula
a. $x^2-3x-10=0$
b. $x^2 -11x+30=0$
Solution
a.
$x^2-3x-10=0$
Comparing this to $ax^2 + bx +c=0$
We have a =1, b=-3 and c =-10
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
or $x=\frac {3 \pm \sqrt {9 +40}}{2}$
$x=\frac {3 \pm 7}{2}$
or
$x=\frac {3 + 7}{2}$ or $x=\frac {3 - 7}{2}$
So roots are x=5 and -2
b. $x^2 -11x+30=0$
Comparing this to $ax^2 + bx +c=0$
a=1, b=-11 and c =30
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
$x=\frac {11 \pm \sqrt {121 -120}}{2}$
$x=\frac {11 \pm 1}{2}$
or
$x=\frac {11 + 1}{2}$ or $x=\frac {11 - 1}{2}$
So
Roots are 5 and 6

Question 3. Find the roots of the quadratic equation using Quadratic formula
a. $x^2 +4x-5=0$
b. $2x^2-7x+3=0$

Solution
a.
$x^2 +4x-5=0$
Comparing this to $ax^2 + bx +c=0$
a=1, b=4 and c =-5
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$  
So
x=1 or -5
b.
$2x^2-7x+3=0$
Comparing this to $ax^2 + bx +c=0$
a=2, b=-7 and c =3
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
So
x=1/2 or 3
 


Question 4
Find the roots using Quadratic Formula
a. $x^2+ (7 - x)^2= 25$
b. $y^2+ (y+2)^2 =580$
c. $11x^2 -31x -6 =0$
d. $9 -y - 10y^2 =0$
e. $14x +4x^2 =2x -5$
f. $3y^2 + 4y=2(y+4)$
g. $2x^2 -5x +3 =0$
h. $\frac {x+1}{x-1} + \frac {x-2}{x+2} =3$ ,$x \neq 1$, $x \neq -2$
i. $x^2 + 5x =-1$
j. $ \sqrt {2x + 9} + x=13$
k. $\frac {1}{a} + \frac {1}{b} + \frac {1}{x} = \frac {1}{a+b+x}$
l. $ \sqrt {2} x^2 + 7x + 5 \sqrt {2}=0$
m. $ \frac {3}{x+1} + \frac {4}{x-1} = \frac {29}{4x-1};x \neq 1,-1,1/4$
Solution
a.
$x^2+ (7 - x)^2= 25$
$x^2 + 49 +x^2 -14x =25$
$2x^2 -14x + 24=0$
$x^2 -7x + 12=0$
Comparing this to $ax^2 + bx +c=0$
a=1, b=-7 and c =12
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
So
x=3 or 4

b.
$y^2+ (y+2)^2 =580$
$y^2 + y^2 + 4 + 4y =580$
$2y^2 + 4y -576=0$
$y^2 + 2y-288=0$
Comparing this to $ay^2 + by +c=0$
a=1, b=2 and c =-288
$y= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
So
y=16 or -18

c.
$11x^2 -31x -6 =0$
Comparing this to $ax^2 + bx +c=0$
a=11, b=-31 and c =-6
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
So
x=3 or -2/11

d.
$9 -y - 10y^2 =0$
$10y^2 + y -9=0$ Comparing this to $ay^2 + by +c=0$
a=10, b=1 and c =-9
$y= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
So
y=-1 or 9/10

e.
$14x +4x^2 =2x -5$
$4x^2 + 12x +5=0$
Comparing this to $ax^2 + bx +c=0$
a=4, b=12 and c =5
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
so x=-1/2 or -5/2

f.
$3y^2 + 4y=2(y+4)$
$3y^2 + 4y = 2y + 8$
$3y^2 + 2y -8=0$
Comparing this to $ay^2 + by +c=0$
a=3, b=2 and c =-8
$y= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
so y=-2 or 4/3

g.
$2x^2 -5x +3 =0$
Comparing this to $ax^2 + bx +c=0$
a=2, b=-5 and c =3
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
so y=3/2 or 1

h.
$\frac {x+1}{x-1} + \frac {x-2}{x+2} =3$
$ \frac { (x+1)(x+2) + (x-2)(x-1)}{(x-1)(x+2)}=3$
$ x^2 + 3x +2 + x^2 -3x + 2= 3(x^2 +x -2)$
$2x^2 +4 = 3x^2 +3x -6$
$x^2 +3x -10=0$
Comparing this to $ax^2 + bx +c=0$
a=1, b=3 and c =-10
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
so x=-5 or 2


i.
$x^2 + 5x =-1$
$x^2 + 5x +1=0$
Comparing this to $ax^2 + bx +c=0$
a=1, b=5 and c =1
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
so,$x = \frac {-5 + \sqrt {21}}{2}$ or $x= \frac {-5 - \sqrt {21}}{2}$

j.
$ \sqrt {2x + 9} + x=13$
$ \sqrt {2x + 9} = 13-x$
Squaring both the sides $2x+9 = (13-x)^2$
$2x+ 9 = 169 + x^2 -26x$ $x^2 -28x +160=0$ Comparing this to $ax^2 + bx +c=0$
a=1, b=-28 and c =160
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
x=20,8
k.
$\frac {1}{a} + \frac {1}{b} + \frac {1}{x} = \frac {1}{a+b+x}$
$\frac {bx + ax + ab}{abx} =\frac {1}{a+b+x}$
$ (bx + ax + ab)(a+b+x) = abx$
$abx + b^2x + bx^2 + a^2 x+ abx+ ax^2 + a^b + ab^2 + abx = abx$
$x^2(a + b) + x(a^2 + b^2 + 2ab) + ab(a+b) =0$
$x^2(a+b)+ x(a+b)^2 + ab(a+b) =0$
Dividing by (a+b)
$x^2 + x(a+b) + ab= 0$
Comparing this to $ax^2 + bx +c=0$
a=1, b=(a+b) and c =ab
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
x=-a,-b

l.
$ \sqrt {2} x^2 + 7x + 5 \sqrt {2}=0$
Comparing this to $ax^2 + bx +c=0$
$a=\sqrt {2}$, b=7 and $c =5 \sqrt {2}$
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
$x = \frac {-7 \pm \sqrt {7^2 -4 \times \sqrt {2} \times 5 \sqrt {2}}}{2\sqrt {2}}$
$x=\frac {-7 \pm \sqrt {49-40}}{2\sqrt {2}}$
or
$x= -\sqrt {2}$ or $x= -\frac {5\sqrt{2}}{2}$

m. $ \frac {3}{x+1} + \frac {4}{x-1} = \frac {29}{4x-1};x \neq 1,-1,1/4$
$ \frac {3(x-1) + 4(x+1)}{(x+1)(x-1)} = \frac {29}{4x-1}$
$\frac {7x +1}{x^2 -1} = \frac {29}{4x-1}$
$ (7x+1)(4x-1) = 29(x^2-1)$
$28x^2 -7x+4x -1 = 29x^2 -29$
$x^2 + 3x-28=0$
Comparing this to $ax^2 + bx +c=0$
a=1, b=3 and c =-28
$x= \frac {-b \pm \sqrt {b^2 -4ac}}{2a}$
x=-7 or 4
Question 5
Solve the below quadratic equation using quadratic formula a. $x^{2} + 4 x = -1$
b. $3 x^{2} + 3 x - 1 = 0$
c. $3 x^{2} + 2 x = 2$
d. $2 x^{2} = 1 -3x$
e. $5 x^{2} = 2 (1-x)$
f. $4 x^{2} + 2 x = 0$
g. $4x( x+ 1) =1$
h. $\frac {1}{x+1} + \frac {2}{x+2} = \frac {4}{x+4},x \neq -1,-2,-4$
i $x^{2} + 2 x - 2 = 0$
j. $4 x^{2} + 4 x - 2 = 0$
k. $3 x^{2} + 4 x + 1 = 0$
l. $4 x^{2} + 4 x - 2=0$
m. $x^{2} + 3 x + 2 = 0$
n. $5 x^{2} + x = 0$
o. $ \frac {16}{x} -1 = \frac {15}{x+1},x \neq 0,-1$
Solution
a. $x = -2 - \sqrt{3}, x = -2 + \sqrt{3}$
b. $x = - \frac{1}{2} + \frac{\sqrt{21}}{6}, x = - \frac{\sqrt{21}}{6} - \frac{1}{2}$
c. $x = - \frac{1}{3} + \frac{\sqrt{7}}{3}, x = - \frac{\sqrt{7}}{3} - \frac{1}{3}$
d. $x = - \frac{3}{4} + \frac{\sqrt{17}}{4}, x = - \frac{\sqrt{17}}{4} - \frac{3}{4}$
e. $x = - \frac{1}{5} + \frac{\sqrt{11}}{5}, x = - \frac{\sqrt{11}}{5} - \frac{1}{5}$
f. $x = - \frac{1}{2}, x = 0$
g. $x = - \frac{1}{2} + \frac{\sqrt{2}}{2}, x = - \frac{\sqrt{2}}{2} - \frac{1}{2}$
h. $x = 2 +2 \sqrt{3}, x = 2 - 2 \sqrt{3}$
i. $x = -1 + \sqrt{3}, x = - \sqrt{3} - 1$
j. $x = - \frac{1}{2} + \frac{\sqrt{3}}{2}, x = - \frac{\sqrt{3}}{2} - \frac{1}{2}$
k. $x = -1, x = - \frac{1}{3}$
l. $x = - \frac{1}{2} + \frac{\sqrt{3}}{2}, x = - \frac{\sqrt{3}}{2} - \frac{1}{2}$
m. $x = -2, x = -1$
n. $x = - \frac{1}{5}, x = 0$
o.$x = - 4, x = 4$
Download Quadratic Formula worksheet as pdf link to this page by copying the following text
Also Read



Reference Books for class 10

Given below are the links of some of the reference books for class 10 math.

  1. Oswaal CBSE Question Bank Class 10 Hindi B, English Communication Science, Social Science & Maths (Set of 5 Books)
  2. Mathematics for Class 10 by R D Sharma
  3. Pearson IIT Foundation Maths Class 10
  4. Secondary School Mathematics for Class 10
  5. Xam Idea Complete Course Mathematics Class 10

You can use above books for extra knowledge and practicing different questions.


Class 10 Maths Class 10 Science

Practice Question

Question 1 What is $1 - \sqrt {3}$ ?
A) Non terminating repeating
B) Non terminating non repeating
C) Terminating
D) None of the above
Question 2 The volume of the largest right circular cone that can be cut out from a cube of edge 4.2 cm is?
A) 19.4 cm3
B) 12 cm3
C) 78.6 cm3
D) 58.2 cm3
Question 3 The sum of the first three terms of an AP is 33. If the product of the first and the third term exceeds the second term by 29, the AP is ?
A) 2 ,21,11
B) 1,10,19
C) -1 ,8,17
D) 2 ,11,20






Note to our visitors :-

Thanks for visiting our website.
DISCLOSURE: THIS PAGE MAY CONTAIN AFFILIATE LINKS, MEANING I GET A COMMISSION IF YOU DECIDE TO MAKE A PURCHASE THROUGH MY LINKS, AT NO COST TO YOU. PLEASE READ MY DISCLOSURE FOR MORE INFO.